Accelerated subcutaneous nodulosis in patients with rheumatoid arthritis treated with tocilizumab: a case series - Rossella Talotta; Fabiola Atzeni; Alberto Batticciotto; Maria Chiara Ditto; Maria Chiara Gerardi; Piercarlo Sarzi-Puttini (Journal of Medical Case Reports, 2018)
Abstract Background Tocilizumab is a monoclonal antibody directed against the interleukin-6 receptor, which is approved for the treatment of moderate-to-severe rheumatoid arthritis. Authors have found that it prevents lung and subcutaneous nodulosis in patients with rheumatoid arthritis but, to the best of our knowledge, there are no data concerning the acceleration of subcutaneous nodulosis during tocilizumab therapy. Case presentation We report for the first time a small case series of five patients with rheumatoid arthritis: a 46-year-old white woman, a 70-year-old white woman, a 63-year-old white woman, a 69-year-old white man, and a 72-year-old white woman (mean age 64 ± 10.6 years); they experienced worsening subcutaneous nodulosis during treatment with intravenously administered tocilizumab. Four of the five patients were positive for rheumatoid factor and five for anti-citrullinated peptide antibodies. All of the patients had previously been treated with various conventional and biological drugs; at the time of our observation, three were taking methotrexate, two hydroxychloroquine, and four were taking prednisone. Tocilizumab 8 mg/kg was administered intravenously every 4 weeks for a mean of 43.4 ± 32.4 months, and led to good disease control in three cases. All of the patients had a history of subcutaneous nodulosis, which considerably worsened during tocilizumab treatment, with the development of new nodules on their fingers, elbows, or in the inframammary fold, tending to ulcerate. The management of this medical event included discontinuation of methotrexate, the administration of steroids, the addition of hydroxychloroquine or colchicine, the use of antibiotics, and surgery. However, neither pharmacological nor surgical treatment was completely effective, as the nodules tended to recur and increased in number and size. Conclusions To the best of our knowledge, this is the first report describing accelerated subcutaneous nodulosis in a small case series of patients with rheumatoid arthritis treated with tocilizumab.